Exploring Properties of Reorientation Surrounding Boundary Transfer and Shape Transformation Procedures. - Holden, Luke (2023)
Recent cue competition literature, such as Buckley, Smith & Haselgrove (2016a), and Herrera et al., (2022), have challenged the notion that learning about the geometric properties of an environment is processed in an encapsulated module. Here, the encoding of spatial features, such as arena boundaries, is thought to be prevented from interaction with nonspatial cues (e.g., landmarks), and therefore immune to standard overshadowing and blocking effects (Gallistel, 1990). Work presented in this thesis aims to further explore the malleability of this idea by exploring properties of reorientation – sometimes in the presence of landmarks.